Implementasi Kebijakan Merger Sekolah dalam Transformasi Manajemen Pendidikan: Analisis Teori Edwards III - Samallo , Suci Elisabeth; Risamasu, Putri Ellen Gracia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study analyzes the implementation of the merger policy of SMA PGRI and SMA KORPRI into SMA Negeri 7 Jayapura using Edwards III's four-dimensional model. This qualitative research employs a case study method with data collection techniques through in-depth interviews with school principals, teachers, students, and officials from the Education Office, as well as observation and policy document analysis. The findings reveal that although the communication dimension was weak in formal socialization, this was compensated by a strong disposition dimension through the principal's transformational leadership. Adequate resource availability and flexible bureaucratic structure supported successful implementation. The uniqueness lies in the bottom-up approach that resulted in a 72.6% increase in student enrollment within two years. This study contributes to understanding that the weight of Edwards III dimensions can vary according to local context, where positive disposition can compensate for weak formal communication.